2019
DOI: 10.1101/719401
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tolerance to NADH/NAD+ imbalance anticipates aging and anti-aging interventions

Abstract: 12Redox couples coordinate cellular function, but the consequences of their imbalances 13 are unclear. This is somewhat associated with the limitations of their experimental 14 quantification. Here we circumvent these difficulties by presenting a new approach that 15 characterizes fitness-based tolerance profiles to redox couple imbalances using an in 16 silico representation of metabolism. Focusing on the NADH/NAD + redox couple in 17 yeast, we demonstrate that reductive disequilibria generate metabolic syndr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…argues that POAG lymphoblasts have a mitochondrial defect which is more modest than LHON lymphoblasts and not severe enough to alter the redox status of the lymphoblast cells [32]. However, several studies in human and animal models have shown that there is evidence that the NAD + /NADH redox state may be a useful biomarker for monitoring and management of several diseases [184][185][186][187][188][189][190][191]. Mitochondrial dysfunction in POAG has been reported by many studies in human lymphocyte, lymphoblast and fibroblast models (Table 1), raising the point that if NAD levels underlie such dysfunction, then one might expect to be able to measure such differences in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…argues that POAG lymphoblasts have a mitochondrial defect which is more modest than LHON lymphoblasts and not severe enough to alter the redox status of the lymphoblast cells [32]. However, several studies in human and animal models have shown that there is evidence that the NAD + /NADH redox state may be a useful biomarker for monitoring and management of several diseases [184][185][186][187][188][189][190][191]. Mitochondrial dysfunction in POAG has been reported by many studies in human lymphocyte, lymphoblast and fibroblast models (Table 1), raising the point that if NAD levels underlie such dysfunction, then one might expect to be able to measure such differences in these cells.…”
Section: Discussionmentioning
confidence: 99%